PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN, PROFITABILITAS, DAN UKURAN DEWAN KOMISARIS TERHADAP NILAI PERUSAHAAN - Elga Cindy Nagayu; Mujiyati Mujiyati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze and seek empirical evidence regarding investment decisions, funding decisions, dividend policy, profitability, and the size of the board of commissioners on firm value. The population in this study is the food and beverages sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2020. By using purposive addition, the sample used in this study were 11 companies in the food and beverages sub-sector. The data analysis method used multiple linear regression analysis with the help of SPSS 21 software. The results found that investment decisions and the size of the board of commissioners had a significant effect on firm value with a sig value. respectively (0.000 < 0.05) and (0.006 < 0.05). Meanwhile, investment decisions, dividend policy, and profitability were found to have no significant effect on firm value with a sig value. each of (0.859 > 0.05); (0.180 > 0.05); and (0.986 > 0.05).